Development of test forms of down passing techniques in sensor-based volleyball games - Indrakasih; Albadi Sinulingga; Ferdinan Lumbaraja; Ahmad Muchlisin Natas Pasaribu (UIR Press, 2022)
The purpose of this study is to develop a form of passing down technique skill test in a sensor-based volleyball game. This research is a research and development (R&D) research. The research steps are: Potential and Problems, Data Collection, Product Design, Design Validation, Design Revision, Product Trial, Product Revision, and User Trial. This development research is first validated by material experts and media experts. The product trial is carried out on volleyball extracurricular students at SMA Nusantara in the open field of PBVSI Deli Serdang, as many as 14 students. Small group test of 7 students, and large group test of 14 students. Type of data collection is with the instrument in the form of a questionnaire. The results obtained from the validation results (a) material experts amounted to 98.3% categorized as very feasible; (b) 98.3% of media experts are categorized as very eligible; (c) small group trial of 86.9% of students in the very appropriate category, (d) large group trial of 91% of students in the very eligible category. The product produced in this development is a sensor and wall target application which is equipped with a user manual. This sensor tool has been declared “very feasible” to be used as a medium or means to help automatically calculate points in the volleyball underpass test. This study also finds some limitations that can be taken into consideration for further research, namely the number of samples studied is still relatively small and supporting facilities are inadequate so that there is a slight delay in taking the exam. Based on the limitations contained in this study, it is hoped that in the future partner researchers can use this research as a reference material for contributions in their research, so that perfection in technological developments in the world of volleyball is achieved.